Evaluating a post-implementation electronic medical record training intervention for diabetes management in primary care. Issue 1 (30th September 2019) - Randhawa, Gurprit Kaur; Shachak, Aviv; Courtney, Karen L; Kushniruk, Andre
Abstract : Objective: This study evaluated the potential for electronic medical record (EMR) video tutorials to improve diabetes (type 1 and 2) care processes by primary care physicians (PCP) using OSCAR EMR. Design: A QUAN(qual) mixed methods approach with an embedded design was used for the overall research study. EMR video tutorials were developed based on the chronic care model (CCM), value-adding EMR use, best practice guidelines for designing software video tutorials and clinician-led EMR training. Results: In total, 18 PCPs from British Columbia, Canada, participated in the study. The video EMR intervention elicited a statistically significant increase in EMR advanced feature use for diabetes care, with a large effect size (ie, F (1, 51)=6.808, p<0.001, partial η 2 =0.286). Conclusion: This small-scale efficacy study demonstrates the potential of CCM-based EMR video tutorials to improve EMR use for chronic diseases, such as diabetes. A larger-scale effectiveness study with a control group is needed to further validate the study findings and determine their generalisability. The demonstrated efficacy of the intervention suggests that EMR video tutorials may be a cost-effective, sustainable and scalable strategy for supporting EMR optimisation and the continuous learning and development of PCPs. Health informatics practitioners may develop video tutorials for their respective EMR/electronic health record software based on theory and best practices for video tutorial design. For patients, EMR video tutorials may lead to improved tracking of processes of care for diabetes, and potentially other chronic conditions.